Online search interface design. - VICKERY, Brian (1993)
Reviews the various aspects of search interfaces by indicating the requirements that must be met if maximum aid is to be offered to the inexperienced searcher; spelling out the knowledge that must be incorporated in an interface if such aid is to be given; describing some of the solutions that have been implemented in experimental and operational interfaces. Discusses some of the problems encountered.